The Relationship Between Mothers’ Knowledge and Attitudes Toward Hypertension Prevention Behavior in South Polongbangkeng District, Takalar Regency, 2026 - Ruqaiyah Ruqaiyah; Darmiati Darmiati; Hadriani Irwan; St. Subriani; Ikrawanty Ayu Wulandari; Rahma Winahyu Jannata; Hukmiyah Aspar; Agusalim Agusalim; Ayatullah Harun (Green Health International Journal of Health Sciences Nursing and Nutrition, 2026)
The effectiveness of hypertension prevention in communities depends critically on individuals’ knowledge of risk factors and their attitudes toward healthy behaviors. This study examines the relationship between mothers’ knowledge and attitudes toward hypertension prevention behavior in South Polongbangkeng District, Takalar Regency, 2026. An observational analytic quantitative design with a cross-sectional approach was employed. A total of 200 mothers were selected as respondents. Data were collected using structured questionnaires assessing knowledge, attitude, and hypertension prevention behavior, then analyzed using chi-square test at a significance level of α = 0.05. Results showed that the majority of respondents had good knowledge (89.0%), good attitudes (91.0%), and good hypertension prevention behavior (77.0%). Statistical tests revealed a significant association between mothers’ knowledge and hypertension prevention behavior (p = 0.000) and between mothers’ attitudes and hypertension prevention behavior (p = 0.000). It is concluded that mothers’ knowledge and attitudes are significantly associated with hypertension prevention behavior. Health workers are recommended to strengthen health education and promotion programs targeting mothers to support hypertension prevention in the community.